A comparison between the performance of teachers; who graduated from Al-Quds Open University and the teachers who graduated from regular studies in universities from the viewpoint of the supervisor and the school principal - Daraghma, Reema Wajeh (Journal of Educational and Psychological Sciences, 2021)
The research aims to identify the performance of teachers, graduates of Al-Quds Open University, and the performance of teachers who are graduates of formal education, according to the standards in Palestinian Commission for Developing the Teaching Profession in the fields of "knowledge and understanding", "professional skills" and "professional trends and values." The researcher used the descriptive and analytical method for its suitability for the objectives of the research. A questionnaire was distributed to the sample of (268) distributed among (182) school principals and (86) educational supervisors. The study found that there are statistically significant differences at (α≤0.05) between the point of view of the educational supervisor and the school principal in favor of the school principal in terms of the availability of professional standards for the teacher and for all these skills. The study also found that teachers who graduated from regular universities possess more knowledge, understanding and professional skills than al-Quds Open University graduates do, while the standards related to professional trends and values ​​were difficult to differentiate between them. The study recommended the need on creating a compulsory educational qualification program in regular and open universities for everyone who wants to work in the teaching profession and to coordinate between universities and the Palestinian Commission for Developing the Teaching Profession on the skills that should be trained and focus on them in university courses related to the teaching profession.
Keywords: performance; profession; standard